2014
DOI: 10.1002/aqc.2461
|View full text |Cite
|
Sign up to set email alerts
|

Use of encounter data to model spatio‐temporal distribution patterns of endangered smalltooth sawfish, Pristis pectinata, in the western Atlantic

Abstract: Sawfishes are among the most threatened fish species globally, with only the smalltooth sawfish (Pristis pectinata) currently regularly observed in the western Atlantic. The National Sawfish Encounter Database (NSED) documents reported encounters with sawfishes in the western Atlantic and contains 4945 reports of 8773 individual P. pectinata (1782–2011).Statistical modelling (generalized linear models and generalized additive models) and kernel density analyses were used to (1) identify spatio‐temporal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Specifically, the application of stable isotope techniques on fin tissues of 2 sympatric elasmobranch species that have well-characterized diets (Snelson et al 1984, Cliff & Dudley 1991, Collins et al 2007), in conjunction with smalltooth sawfish, a variety of consumer species, and the 18S rRNA gene analysis has provi ded evidence to support the hypothesis that smalltooth sawfish feed primarily on fishes regardless of life stage. Further, this reliance on fish prey persists even though smalltooth sawfish and bull sharks Carcharhinus leucas move from estuaries to coastal habitats during their onto geny (Simpfendorfer et al 2005, Scharer et al 2012, Carlson et al 2014, Waters et al 2014. Moreover, our results support those of previous studies that suggested smalltooth sawfish and bull sharks partition their habitat while in the Charlotte Harbor estuarine system during their early life histories (see below).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Specifically, the application of stable isotope techniques on fin tissues of 2 sympatric elasmobranch species that have well-characterized diets (Snelson et al 1984, Cliff & Dudley 1991, Collins et al 2007), in conjunction with smalltooth sawfish, a variety of consumer species, and the 18S rRNA gene analysis has provi ded evidence to support the hypothesis that smalltooth sawfish feed primarily on fishes regardless of life stage. Further, this reliance on fish prey persists even though smalltooth sawfish and bull sharks Carcharhinus leucas move from estuaries to coastal habitats during their onto geny (Simpfendorfer et al 2005, Scharer et al 2012, Carlson et al 2014, Waters et al 2014. Moreover, our results support those of previous studies that suggested smalltooth sawfish and bull sharks partition their habitat while in the Charlotte Harbor estuarine system during their early life histories (see below).…”
Section: Discussionsupporting
confidence: 88%
“…Shallow, seagrass-covered carbonate mud banks are a common feature in the bay, which is inhabited by the greatest concentration of adult smalltooth sawfish in its range (Poulakis & Seitz 2004, Waters et al 2014. Florida Bay contains mud bottom, hard bottom, and macroalgal communities and has extensive red mangrove shorelines (Fernald & Purdum 1998).…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional fishing surveys using fishing gear (gillnets, lines) have proved useful (Thorburn et al 2007, Wiley & Simpfendorfer 2007, but are time consuming, logistically difficult in remote areas, expensive and may not detect animals even if they are present. Public encounter data have also been used to determine the distribution and habitat associations of smalltooth sawfish Pristis pectinata in Florida (Poulakis & Seitz 2004, Wiley & Simpfendorfer 2010, Waters et al 2014). This approach is less expensive, but relies on the distribution of observational effort, considerable outreach, the ability of the public to identify species correctly and their willingness to report encounters (particularly given the apprehension over reporting the capture of a listed protected species) to gather sufficient data (Wiley & Simpfendorfer 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It currently occurs primarily in southwest Florida, U.S. [6], where it may have stabilized and started to recover (http://www.iucnredlist. org/details/18175/0 ).…”
Section: Facultative Parthenogenesis In a Critically Endangered Wild mentioning
confidence: 99%